1995
DOI: 10.1177/107769909507200307
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Viewing and Enjoyment of Reality-Based and Fictional Crime Shows

Abstract: Telephone surveys were conducted in Virginia and Wisconsin to explore attitudinal predictors of exposure to and enjoyment of reality-based and fictional crime programs. Punitive attitudes about crime, higher levels of racial prejudice, and higher levels of authoritarianism were associated w'th more frequent viewing and greater enjoyment of reality-based programming, but were unrelated to enjoyment of fictional programming. Reality-based viewing and enjoyment were also more common among younger respondents, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 0 publications
1
50
1
Order By: Relevance
“…First, most studies are cross-sectional and, therefore, the causal order of variables cannot be derived from these surveys. While some scholars have found that media use predicts racial attitudes (Armstrong, Neuendorf, & Brentar, 1992;Dixon, 2008), others have demonstrated that prejudiced individuals use media programs that portray ethnic minorities negatively (Oliver & Armstrong, 1995;Schemer, 2012a). These findings highlight the fact that the causal direction of variables cannot be determined using cross-sectional data.…”
mentioning
confidence: 95%
“…First, most studies are cross-sectional and, therefore, the causal order of variables cannot be derived from these surveys. While some scholars have found that media use predicts racial attitudes (Armstrong, Neuendorf, & Brentar, 1992;Dixon, 2008), others have demonstrated that prejudiced individuals use media programs that portray ethnic minorities negatively (Oliver & Armstrong, 1995;Schemer, 2012a). These findings highlight the fact that the causal direction of variables cannot be determined using cross-sectional data.…”
mentioning
confidence: 95%
“…In addition, reality television is of interest to media effects researchers, who seek to understand if and how it shapes viewers' thoughts, beliefs, and attitudes about the world around them (e.g., Cavendar & Bond-Maupin, 1993;Oliver & Armstrong, 1995). Studying the personality antecedents and motivations for viewing reality television will allow researchers to better understand who is likely to be drawn to reality television and with what potential impact (Rubin, 2002).…”
mentioning
confidence: 98%
“…Bryant and his colleagues (1981) found that heavy viewing of action-adventure programs increased fearfulness and anxiety levels, especially if justice did not ultimately prevail in the viewed programs. Oliver and Armstrong (1995) found higher levels of racial prejudice, as well as punitive attitudes about crime, associated with frequent viewing and greater enjoyment of reality-based programming -though a cultivation effect did not hold for fictional programming. More recently, Kahlor and Eastin (2011) found that large amounts of rape-related content in soap operas and crime dramas "independently cultivate perceptions related to rape and sexual assault" (227), with viewers of those genres more likely to accept rape myths and overestimate false accusations.…”
Section: Attitudinal Effects: Cultivation Theorymentioning
confidence: 81%